A Proposal of Revised Curriculum to Circumvent the Impact of COVID Restrictions on Final Year Medical Students - Khalid Mehmood, Rao; Gaurav, PAWAR; Akhtar, Kaleem; Dar, Farooq; Akhtar Hamid, Muhammad (International Journal of Coronaviruses, 2022)
Medical education has been extraordinarily disrupted during the COVID-19 era worldwide. The pandemic limited routine ward or patient-based medical education. These limitations have resulted in new challenges for medical students, especially the final year students in completing their mandated curriculum. We are suggesting a revised curriculum for final year medical students, by following which we can address COVID restriction while making sure all competencies have been achieved by students. This revised curriculum centers around the usual placement of students in Surgical Assessment Unit (SAU), however all students will be posted in simulation wards/labs on their turn to enhance and consolidate their understanding and learning of common surgical cases in these wards, so that they can replicate these skills in SAU and wards on their turns. This article highlights how the proposed curriculum addresses the learning needs of final year medical students in their surgery rotation. The article will also summarize the critical appraisal process of our curriculum in the context of curriculum design theories. Finally, the article will highlight the quality assurance measures adhered to while developing the curriculum.
Keywords: COVID-19; medical education; curriculum; surgery residency